И.ЮСУПОВ ЛИРИКАСЫНДА ЖЕКЕ АВТОРЛЫҚ ЭПИТЕТЛЕРДИҢ ҚОЛЛАНЫЛЫЎЫ - Өтепбергенова, Г. (FAN va JAMIYAT, 2025)
The article provides information about the epithet descriptive tool. In addition, the types of epithets, their role in the works of I. Yusupov, and the criteria of activation in the artistic text are discussed. With the help of an epithet, a unique delicacy, expressiveness and depth are achieved.